Experimental Research on Bending Bearing Capability of Grouted Double Mortise-Tenon Joint for Prefabricated Metro Station Structure - Xiuren Yang; Fang Lin; Meiqun Huang (Advances in Civil Engineering)
The grouted mortise-tenon joint, invented as the connection between the large prefabricated elements, is the most important component in the prefabricated underground structures. This paper conducts analysis of load-carrying capacity performance and failure mode with 1 : 1 prototype test in key working direction of different double mortise-tenon joint types for the prefabricated metro station. The resistance moment is developed and used to analyze the bending bearing characteristic curve, and the corresponding test results of each stage of the characteristic curve are described in detail. In addition, the bending bearing performance of different types of double-tenon joints under different load conditions is compared. The test results clarify the ultimate failure mode of double-tenon joint and the variable bearing capacity characteristics of the joint with the increase in axial load and explain the bearing performance of each stage. It is also found the auxiliary pretightening device is helpful to delay the appearance of cracks and improve the bearing capacity, especially when it is set on the tension side. The research results have important application value for the joint design of prefabricated metro station structures.